2012
DOI: 10.1016/j.str.2012.04.022
|View full text |Cite
|
Sign up to set email alerts
|

An Internal Water-Retention Site in the Rhomboid Intramembrane Protease GlpG Ensures Catalytic Efficiency

Abstract: SUMMARY Rhomboid proteases regulate key cellular pathways, but their biochemical mechanism including how water is made available to the membrane-immersed active site remains ambiguous. We performed four prolonged molecular dynamics simulations initiated from both gate-open and gate-closed states of Escherichia coli rhomboid GlpG in a phospholipid bilayer. GlpG was notably stable in both gating states, experiencing similar tilt and local membrane thinning, with no observable gating transitions, highlighting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 31 publications
5
66
0
Order By: Relevance
“…The exact order of events, and what triggers each step, remain speculative. Membrane thinning surrounding GlpG as observed in molecular dynamics simulations is illustrated (Bondar et al, 2009; Zhou et al, 2012), although its functional consequence remains unclear. Structures 2IC8 (closed GlpG), 2NRF (open GlpG), 1MOX (Spitz-EGF), and 2TGF (TGFα-EGF) were used to diagram the model. DOI: http://dx.doi.org/10.7554/eLife.00173.016…”
Section: Discussionmentioning
confidence: 94%
“…The exact order of events, and what triggers each step, remain speculative. Membrane thinning surrounding GlpG as observed in molecular dynamics simulations is illustrated (Bondar et al, 2009; Zhou et al, 2012), although its functional consequence remains unclear. Structures 2IC8 (closed GlpG), 2NRF (open GlpG), 1MOX (Spitz-EGF), and 2TGF (TGFα-EGF) were used to diagram the model. DOI: http://dx.doi.org/10.7554/eLife.00173.016…”
Section: Discussionmentioning
confidence: 94%
“…The nonnative region contains many residues on the "front face" of GlpG, a region that likely needs to be stable to counterbalance the more flexible active face. Loops 1-3 (the nonnative region) have many packing interactions with GlpG's internal core, whereas loops 4-5 (outside the nonnative region) line the flexible TM5 and are dynamic in molecular dynamics simulations (40). However, there is not a simple stabilization pattern: one of the critical stabilizing residues in GlpG found from Baker and Urban's heat-mapping study (28) is found in the folding nucleus (E166) and another in the nonnative region (R137).…”
Section: An Extensive Nonnative Region Of Folding: Restrictions In Tomentioning
confidence: 99%
“…Thus, understanding the molecular mechanism by which ␥-secretase produces A␤ 42 is important for the development of therapeutic agents against AD. ␥-Secretase comprises four transmembrane proteins: presenilin (PS), anterior pharynx-defective 1, Nicastrin, and presenilin enhancer 2 (Pen-2; Takasugi et al, 2003). PS is an aspartic protease subunit that shows proteolytic activity and autoproteolysis to generate Nand C-terminal fragments (NTF and CTF, respectively) on formation of the full complex.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike PS, mmPSH can catalyze the proteolysis of substrates without additional cofactors, and, furthermore, it is difficult to resolve the crystal structure of multimeric membrane proteins. We previ-ously analyzed the structure of membrane-embedded, proteolytically active PS1 using the substituted cysteine accessibility method (SCAM) and cross-linking experiments (Sato et al, , 2008Takagi et al, 2010). SCAM enables identification of the hydrophilic environment by the accessibility of sulfhydryl reagents to cysteine residues (Cys) introduced at a desired position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation